EFEKTIVITAS PELATIHAN KOGNITIF-PERILAKU UNTUK MENURUNKAN KECEMASAN BERBICARA DI DEPAN UMUM PADA SISWA KELAS XI - Komarudin, Komarudin (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstract: The research aimed to find out the effectiveness of Cognitive-Behavioral Training for turning down the anxiety of public speaking for students in 11 rd grade social in MAN II Yogyakarta. The data collecting technique used the anxiety of public speaking scale. The data were analysed statistically by used Wilcoxon Sign rank test with SPSS 16. The data analysis result was the probability of Z value was -2,023 (p<0,05). It meant there was significant effect from Cognitive-Behavioral Training for turning down the anxiety of public speaking for students in 11 rd grade social in MAN II Yogyakarta. The students‟ anxiety of public speaking turned down after they had treatmen. It could be seen from the result of post-test lower than pre-test. There is escalation in the post-test with mean 15,61.Keyword: cognitive-behavioral training, the anxiety of public speaking